Implantable vascular access port-associated bloodstream infection caused by Rhizobium radiobacter: a case report - Karadağ-Öncel, Eda; Ozsürekci, Yasemin; Aytaç, Selin; Kara, Ateş; Cengiz, Ali Bülent; Ceyhan, Mehmet (The Turkish Journal of Pediatrics, 2013)
Rhizobium radiobacter is an uncommon opportunistic pathogen present in soil. It has been particularly associated with indwelling intravascular devices in immunocompromised patients. Reported herein is a case of R. radiobacter bloodstream infection associated with an implantable vascular access port, which was easily controlled with antimicrobial treatment and did not require removal of the intravascular device, in a child diagnosed with acute lymphoblastic leukemia. Also included is a review of the pertinent literature regarding the clinical presentation and management of R. radiobacter infections in the childhood period.